BENDERA DI HIZBUT TAHRIR INDONESIA DAERAH ISTIMEWA YOGYAKARTA (KAJIAN KONTEKS SEJARAH, KONTEKS BUDAYA, DAN ESTETIKA SEMIOTIS) - Junaedi, Deni (Jurnal Kawistara, 2012)
This paper discusses on ags used by Hizb ut-Tahrir Indonesia Yogyakarta (HTI DIY). This organization uses two types of ag: liwa and rayah. The color of the liwa is white and the color of the rayah is black. Upon both the profession of faith (shahada) is written in Arabic Calligraphy. Historically speaking, the Prophet Muhammad used the liwa and the rayah. Politically speaking, both ags are intended for use as the ag of the nwe caliphate to which HizbI ut-Tahrir (HT) aspires. HTI DIY con rms that liwa and rayah are not their ags but ags of Islam. The semiotic aesthetics study of the ags includes the study of aesthetic object, aesthetic values, and aesthetics experience. As aesthetic objects, the liwa and rayah show varieties. Aesthetic values of those ags consist of a symbolic value, one which refers to Islam and the Caliphate; iconic value, i.e.the imitation of the Prophet Muhammadâs ags; and indexical value indicating the activity of the HTI DIY. Aesthetic experiences of the ags experienced by the HTI DIY activists are in the form of the emotional effects.